Trends in aquaculture sciences: from now to use of nanotechnology for disease control - Luis, Angélica Irasema Sibaja [UNESP]; Campos, Estefânia Vangelie Ramos [UNESP]; de Oliveira, Jhones Luiz [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Wiley, 2019)
Aquaculture is increasingly important in global food production. Consequently, the control of diseases in aquaculture is essential, due to the potential environmental impacts, notably in terms of the states of health of freshwater bodies and the oceans. In this study, we review the possible uses of different management systems, highlighting essential oils and novel nanotechnological strategies, for the control of diseases in aquaculture.
Keywords: aquaculture; disease control; environment; fish diseases; nanotechnology